Assessment of nutritional status, nutrient intake, physical activity and quality of life among overweight & obese female government staffs in Kota Bharu, Kelantan. - Ayoub, Aqila (Universiti Sains Malaysia, 2017)
Assessment of nutritional status, nutrient intake, physical activity and quality of life were carried out among 160 overweight and obese women government staffs in Kota Bharu, Kelantan. Data was collected using a questionnaire which included socio-demographic characteristics, the International Physical Activity Questionnaire (IPAQ), 24-hour dietary recall and Impact Weight Quality of Life (IWQOL) questionnaire. Body mass index, waist circumference, weight and height were measured using standardized methods. Almost half of the respondents (36.9 %) were within age of 30-39 years. Majority of the respondents were Malay (99.4%) and followed by Chinese (0.6%). Mean weight, height and BMI of the respondents were 72.3 ± 9.12 kg, 1.55 ± 0.06 cm, and 30.0 ± 3.33 kg/m2 respectively. Based on WHO classification, 60.0% of respondent were overweight and 40% of respondents are obese respectively. The waist circumference of respondents for normal and obese individuals are 1.9% and 98.1% respectively. The mean total physical activity score was high in obese group (17171.63 ± 13353.24) than overweight group (14238.23 ± 9963.04). Furthermore, the mean total calorie intake of respondents for overweight (1631.13 ± 458.18 kcal) was higher than obese (1513.03 ± 475.68 kcal). Significant linear relationship was found between protein intake in sexual life of quality of life (b=0.13, 95% CI= 0.001, 0.258, p < 0.048), age in public distress of quality of life (b= -0.386, 95% CI= -0.006, -0.106, p < 0.007) and individual income in public distress of quality of life (b= -0.002, 95% CI= -0.003, 0.000, p < 0.024). This indicate that age, individual income and protein intake can be used a predictor for quality of life. However, there is no association was identified between physical activity and BMI with quality of life.